2006
DOI: 10.1207/s15327752jpa8601_05
|View full text |Cite
|
Sign up to set email alerts
|

The Assessment of Emotional Intelligence: A Comparison of Performance-Based and Self-Report Methodologies

Abstract: We assessed the patterns of convergent validity for the Mayer-Salovey-Caruso Emotional Intelligence Test (Mayer, Salovey, & Caruso, 2002), a performance-based measure of emotional intelligence (EI) that entails presenting problems thought to have correct responses, and a self-report measure of EI (Schutte et al., 1998). The relations between EI and demographic characteristics of a diverse community sample (N = 223) concurred with previous research. However, the performance-based and self-report scales were not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
139
1
30

Year Published

2006
2006
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 208 publications
(186 citation statements)
references
References 39 publications
16
139
1
30
Order By: Relevance
“…Matthews et al also found a small negative relationship with avoidance-focused coping (r = -.16). However, Goldenberg, Matheson, and Mantler (2006) found a positive relationship between problem-focused coping and the emotion management branch of the MSCEIT (with no significant relationship for the EI, Coping, and Academic Success 9 other branches). Bastian et al (2005) found no relationship between any of the MSCEIT branches and total scores on the COPE.…”
Section: Coping and Emotional Intelligencementioning
confidence: 74%
“…Matthews et al also found a small negative relationship with avoidance-focused coping (r = -.16). However, Goldenberg, Matheson, and Mantler (2006) found a positive relationship between problem-focused coping and the emotion management branch of the MSCEIT (with no significant relationship for the EI, Coping, and Academic Success 9 other branches). Bastian et al (2005) found no relationship between any of the MSCEIT branches and total scores on the COPE.…”
Section: Coping and Emotional Intelligencementioning
confidence: 74%
“…In contrast, written self-report questionnaires can be used to determine one's perceived emotional intelligence, the score from which is often referred to as one's emotional quotient (EQ). Although some have interpreted the finding that selfreport measures of EQ are poorly related to performance tests (Brackett & Mayer, 2003;Goldenberg, Matheson, & Mantler, 2006) as suggesting a weakness in selfreports, this remains to be confirmed. Nevertheless, selfreport measures have proven valuable to researchers in their affordability and efficiency, as some studies simply cannot accommodate performance-based testing.…”
Section: International Journal Of Transpersonal Studies 12mentioning
confidence: 96%
“…As was noted (King & DeCicco, 2009), no performance-based measure of spiritual intelligence currently exists. Although there is evidence to suggest that performance-based measures of intelligence are more valid than self-report measures (Brackett & Mayer, 2003;Goldenberg et al, 2006), too little is understood about spiritual intelligence to develop performance-based measures at this time. Indeed, such a task is reasonably easier when it comes to the verbal and mathematical abilities, for which objective criteria are well established.…”
Section: International Journal Of Transpersonal Studies 17mentioning
confidence: 99%
“…Perhaps studies that claim the continued development of emotional understanding and regulation in adulthood (Chapman & Hayslip, 2006;Extremera, Fernández-Berrocal, & Salovey, 2006;Goldenberg, Matheson, & Mantler, 2006;Kafetsios, 2004;Van Rooy, Alonso, & Viswesuaran, 2005), could in some way justify this result. They point out that the ability to attend to and clarify emotions is developed first and later, over time, the emotional regulation is developed.…”
Section: Discussionmentioning
confidence: 99%